Coronary-Artery Bypass Grafting - J. Alexander; P. Smith (Кардіохірургія та інтервенційна кардіологія)
This review deals with the surgical technique and the evidence-based data on the coronary artery bypass grafting (CABG), and its complications. The advances of CABG over percutaneous coronary intervention and drug therapy in various clinical situations are analyzed. It is stated, that the most significant clinical improvement after CABG could be expected is case of careful selection of patients for this surgery.